Pengaruh Sales Growth, Leverage dan Fix Asset Intensity Terhadap Tax Avoidance dengan Institutional Ownership sebagai Variabel Moderasi - Purba, Eva Tesanika Br; Taufik, Taufeni; A, Al Azhar (Media Akuntansi Perpajakan, 2025)
This research aims to determine and examine the effect of sales growth, leverage, and fixed asset intensity on tax avoidance and to determine whether institutional ownership can moderate the effect of sales growth, leverage and fixed asset intensity on tax avoidance. This research uses a quantitative approach using secondary data contained in financial statements. The sample of this research was the manufacturing company in the primary consumer goods sector listed on the indonesia stock exchange in 2021-2023. Sampling using purposive sampling and obtained a sample of 57 companies. Data analysis techniques were carried out using multiple regression analysis and moderated regression analysis using SPSS software version 25. The results of this research indicate that sales growth and leverage have a significant effect on tax avoidance, while fixed asset intensity does not have a significant effect on tax avoidance. Institutional ownership can moderate the effect of sales growth and leverage on tax avoidance, while improving asset intensity with institutional ownership as a moderating variable has no effect on tax avoidance. These findings support agency theory and emphasize the importance of the role of institutional ownership as a supervisor of management in preventing tax avoidance practices that can be detrimental.